Ibn Rushed Intellectual Fighter to The Limit - الصالح, إيمان (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
the rational philosophy of Averroes (Ibn Rushed) that he elaborated and implemented in many applications is one of the important human achievements in the field of knowledge. It takes as starting point the crystallization, organization and intensification of Aristotle’s works, completing what he only planned, consequently showing out the various aspects of his philosophy, adding to it new points of view that integrate together, leading to a kind of philosophy equipped with all terms of scientific knowledge.